Cancer Cells Treated by Clusters of Copper Oxide Doped Calcium Silicate - Mostafa Mabrouk; Sayed Hamed Kenawy; Gehan El Tabie El-Bassyouni; Ahmed Abd El-Fattah Ibrahim Soliman; Esmat Mahmoud Aly Hamzawy (Tabriz University of Medical Sciences, 2019)
Purpose: Different compositions of copper oxide (CuO)-doped calcium silicate clusters wereused to treat the cancer cells.Methods: The influence of CuO content on the morphology, drug delivering ability,physicochemical properties and cytotoxicity was investigated.Results: The microcrystalline structure revealed the decrement of the size from (20-36 nm) to(5-7 nm) depending on the copper content percentages. Drug delivering ability of doxycyclinehyclate (Dox) was down regulated from 58% to 28%in the presence of the CuO. The inclusionof CuO and Dox didn't show any remarkable changes on the physicochemical properties of theCuO-doped calcium silicate nanoparticles.Conclusion: The CuO-doped calcium silicate sample (5 weight %) exhibited great cytotoxicityagainst the tested cell lines compared to the CuO-free sample. CuO-doped materials displayedsignificant anticancer effect; this sheds light on its implication in the treatment of cancer.